THE ROLE OF THE JAGOI BABANG CROSS-BORDER POST IN IMPROVING THE SOCIAL WELFARE OF BORDER COMMUNITIES - Hartati Hartati; Sofyan Cholid; Muhamad Yanuar Hadi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
Border areas have a strategic role in national development, including through the State Border Post which is designed to improve connectivity between countries and the social welfare of the community. This study aims to analyze the role of the Jagoi Babang State Border Post in supporting socio-economic development in the border area of ​​Bengkayang Regency, West Kalimantan. Using thematic analysis methods based on secondary data, this study explores community perceptions, policy effectiveness, and key challenges in managing the State Border Post. The results of the study indicate that although the existence of the State Border Post has increased access to basic infrastructure, such as electricity and roads, limited coordination between agencies and low skills of local communities are major obstacles. This study is relevant to fill the literature gap in border area management, as well as providing strategic recommendations for the government in increasing the role of the State Border Post to be more inclusive and sustainable.